Pengaruh Pelimpahan Wewenang Terhadap Kualitas Pelayanan di Kantor Kecamatan Cileunyi - Usep Muhammad Abdul Qohar; Asep Hidayat (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
AbstractThe implementation of effective and efficient service quality in the Sub-district office environment illustrates the implementation of delegation of authority given by the Regent to the District Head. Where the District Head carries out some of the functions the Regent gives to provide services to the community in the sub-district environment. As regulated by the Regent of Bandung Regency No. 60 of 2011 concerning the delegation of authority for some of the Regent's affairs to the District Head. But in reality on the ground, there are some problems regarding services that have not yet been implemented which have resulted in ineffective implementation of services to the community. The purpose of this study is to determine how much influence the authority, responsibility and accountability regarding the transfer of authority in the District of Cileunyi. This study uses a theory from Hasibuan which consists of three authority delegation variables, namely authority, responsibility, accountability. As for service quality using the theories of Zeithaml, Parasuraman, Leonard quoted by Hardiyansyah. The sample used was 30 employees in the Cileunyi District office. The research method used is a quantitative method with an associative approach that aims to determine the relationship of one or more variables, namely the influence of delegation of authority to the quality of service in the district of Cileunyi. The results of this study indicate that the influence of delegation of authority (authority, responsibility, accountability) has an influence on the quality of service in the Cileunyi District office of 0.555 or 55.5%, then it is included in the